Breastfeeding duration and associated factors between 1960 and 2000 - Danielle Soares de Oliveira; Cristiano S. Boccolini; Eduardo Faerstein; Eliseu Verly-Jr
Abstract Objective: To describe a historical series on the median duration of breastfeeding in a population of mothers whose children were born from the 1960s onwards, identifying factors associated with the interruption of breastfeeding in each decade. Methods: Data were analyzed from the Pró-Saúde Study, a longitudinal epidemiological investigation started in 1999 among technical and administrative employees of a university in the state of Rio de Janeiro. Breastfeeding duration was collected in two study phases: Phase 1 (1999), and phase 4 (2011-2012). Of these, those who had at least one child and reported the duration of breastfeeding for the first child were selected (n = 1539). To analyze the duration of breastfeeding, survival curves were constructed using the Kaplan-Meier method and the effect of covariates on the duration of breastfeeding was estimated by Cox regression model. Results: It was found that the median duration of breastfeeding was higher in the 1990s and 2000s and lower in the 1970s, compared to the 1960s. In addition, there was an association between higher income and maternal age with breastfeeding interruption, which was focused in the 1970s. Conclusion: There was shorter duration of breastfeeding in the 1970s compared to the 1960s. Increased duration and prevalence of breastfeeding from the 1970s onwards coincided with the national trend and the promotion of this practice since 1980.